2014
DOI: 10.1002/2013gl059178
|View full text |Cite
|
Sign up to set email alerts
|

Improved constraints on seismic source parameters of the 2011 Tohoku earthquake from GRACE gravity and gravity gradient changes

Abstract: A new approach of using only the north component of gravity change from Gravity Recovery and Climate Experiment (GRACE) data reveals that a substantially higher spatial resolution of the observed seismic deformation following the 2011 Tohoku earthquake is achievable at 333 km or longer. Here we show that GRACE-observed north component of gravity change, À17.6 ± 1.1 μGal, and the corresponding gravity gradient change, e.g., Txz at 1.25 ± 0.09 mEötvös, agree well with seismic/GPS model predictions. Localized Sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 33 publications
7
30
0
Order By: Relevance
“…The TVG signal solutions are presented in Figure . The coseismic least squares solution (Figure a) and the EOF solution (Figure b, accounting for 92% of the total variance) match well in spatial pattern and furthermore agree well with previous studies (e.g., Cambiotti & Sabadini, , ; Dai et al, ; Han et al, , ; Matsuo & Heki, ; Zhou et al, ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The TVG signal solutions are presented in Figure . The coseismic least squares solution (Figure a) and the EOF solution (Figure b, accounting for 92% of the total variance) match well in spatial pattern and furthermore agree well with previous studies (e.g., Cambiotti & Sabadini, , ; Dai et al, ; Han et al, , ; Matsuo & Heki, ; Zhou et al, ).…”
Section: Resultssupporting
confidence: 89%
“…Matsuo and Heki () concluded that the earthquake detection threshold using the least squares fit appeared to lie around Mw 8.6. Han et al () could hardly detect the 2007 Bengkulu event of Mw 8.5, whereas Dai et al () managed that by means of more sophisticated GRACE data processing taking advantage of the orbit configuration. Tanaka et al () reported the possible detection of the 2013 Okhotsk event of Mw 8.3.…”
Section: Discussionmentioning
confidence: 99%
“…After coregistering all DSMs to a reference DSM, a linear model with least squares adjustment is used to obtain elevation time series and estimate the elevation change caused by the volcanic eruption, as well as to quantify the uncertainties. The linear model is defined by a constant value and a change of elevation using the Heaviside step function (Dai et al, ); that is, y=a+b×H()tte, where a is a time‐invariant constant in units of meters, b is the estimated elevation change, in meters, and t e the epoch of eruption, in years. The Heaviside step function is then defined as follows: H()tte={00.75emt<te0.50.75emt=te10.75emt>te. …”
Section: Data Processingmentioning
confidence: 99%
“…Coseismic gravity changes of very large earthquakes have been detected by Gravity Recovery and Climate Experiment (GRACE) since its launch in 2002, including the 2004 M w = 9.1 Sumatra-Andaman earthquake (e.g., Han et al 2006;Chen et al 2007), 2010 M w = 8.8 Maule (Central Chile) earthquake (e.g., Han et al 2010;Heki and Matsuo 2010), 2011 M w = 9.0 Tohoku-Oki earthquake (e.g., Matsuo and Heki 2011;Han et al 2011;Wang et al 2012a;Zhou et al 2012;Sabadini 2012, 2013;Dai et al 2014), and the 2012 M w = 8.6 Wharton basin earthquake off-Sumatra (Han et al 2013). Attributing to the wide availability of various seismologic and geodetic observations for the Japan areas, the slips associated with 2011 Tohoku-Oki earthquake have been well constrained, using seismic wave data (e.g., Hayes 2011;Shao et al 2011;Suzuki et al 2012), land global positioning system (GPS) and seafloor bathymetry data (e.g., Chang and Chao 2011;Ito et al 2011;Suito et al 2011;Sato et al 2011;Sleep 2012), InSAR data (e.g., Kobayashi et al 2011), etc.…”
Section: Introductionmentioning
confidence: 99%